Tourist tax: first results and prospects - Savtsova, A. V.; Domarev, A. A.; Volostnikov, M. E.; Petrovskaya, A. A.; Pogozheva, A. A. (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. Starting from January 1, 2025, municipalities have the right to impose a tourist tax. For this purpose, a new chapter entitled Tourist Tax has been included in the Tax Code of the Russian Federation. The decision on the introduction of a tourist tax and its amount is made by municipalities. They can also set additional benefits. The mentioned fee is charged for temporary accommodation services. The tax provides for a gradual increase in rates: from 1% of the price of accommodation in 2025, with an addition of 1% per year until 2029 (then no more than 5%). Municipalities can set differentiated rates based on the season and the category of accommodation facilities. At the same time, there is a minimum tax. Such rates can be applied to calendar months that make up tax periods (quarters). Despite the fact that the Federal Tax Service of Russia and the Ministry of Finance have explained the nuances of calculating taxes and using cash registers, in practice, since the tax is new and many taxpayers face its collection for the first time, there are questions that require clarification and in-depth study. Goal. Assessment of the organizational and legal aspects of the introduction of a tourist tax in the Stavropol Territory, analysis of the regulatory framework, administrative and control procedures, identification of possible risks and measures to minimize them. Materials and methods. The study is based on the analysis of open access data, including: the essence and nature of the tourist tax, the history of its application in Russia and foreign experience, the main parameters of the budgets of municipalities of the Stavropol Krai, the legal basis of the tourist tax. Results and discussion. The study found that 508 accommodation facilities with 24,000 rooms have been prepared for tourists in the region for the holiday season. Guests of the region will be able to visit three thousand monuments and more than 300 tourist routes. To maintain and develop all these facilities, huge financial resources are needed, some of which can be provided by the tourist tax. Conclusion. In the course of the study, it was found that the tourist tax is levied on the accommodation facilities, and not on the vacationers themselves. The money goes to the budget of the local administration without a specific purpose, unlike the resort fee, which was sent to the budget of the constituent entity of the Russian Federation, this is a new tax, and some nuances arise when calculating it.